FAKTOR-FAKTOR PENYEBAB RENDAHNYA PRESTASI BELAJAR SISWA - Putri, silpia deka; ., Neviyarni . (Universitas Negeri Padang, 2013)
Causes of low student achievement is influenced by two factors, namely internal and external factors. The reality on the ground, a lot of students who have low academic achievement, students often go out into the current study. Research purposes to describe the factors causing low class VIII student achievement. The form is a descriptive study, results revealed low achievement on internal factors, namely: the most prominent motivational factor to the low student achievement, while the external factors are: the relation of factors the most prominent member of the family to be the cause of low student achievement. Keywords: Causative Factors; The Low Student Achievement